EKSISTENSI KRITIK TEATER DI MEDIA CETAK: SEBUAH TINJAUAN KRITIS - Nur Sahid (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
This research aim to as follows: a) wish to know the writing format criticize theatre in mass media print; b) wish to know the elementary difference among or between criticism masterpiece writed by critic of have background to of actor of theatre with have background to of have background to of journalist. The result of research got by some conclusion of following. Writer of critic of theatre from journalist more emphasizing of aspect of event of show of theatre fulfilling journalistic standard which concept 5W+1H (what, where, when, who, why and how). Nuance differ very felt at critics of theatre of masterpiece of all observer of theatre which is non journalist of like Putu Wijaya, Afrizal Malna and Syu’ bah Asa. In their analisys theatre staging can lay open most of all theatre aspect. Every aspect laid open by detail.Keywords: theatre of criticism, theatre, journalist, artistic, art